2017
DOI: 10.1080/21663831.2017.1405371
|View full text |Cite
|
Sign up to set email alerts
|

Back stress in strain hardening of carbon nanotube/aluminum composites

Abstract: As demonstrated by the loading-unloading tests and the modeling of the grain size effect and the composite effect, mainly owing to the back stress induced by CNTs, carbon nanotube/aluminum (CNT/Al) composites exhibit higher strain hardening capability than the unreinforced ultrafinegrained Al matrix. The back stress induced by CNTs should arise from the interfacial image force and the long-range interaction between statically stored dislocations and geometrically necessary dislocations around the CNT/Al interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…As discussed above, back stress strengthening and work hardening have been believed responsible for the superior combination of strength and ductility of HS materials [1,2,39,61] as well as the Bauschinger effect [36,38,47,50]. To analyze this issue, let's look at the dislocation model of GND pile-up at an HS domain boundary in Figure 3.…”
Section: Issues With the Back Stress Conceptmentioning
confidence: 99%
“…As discussed above, back stress strengthening and work hardening have been believed responsible for the superior combination of strength and ductility of HS materials [1,2,39,61] as well as the Bauschinger effect [36,38,47,50]. To analyze this issue, let's look at the dislocation model of GND pile-up at an HS domain boundary in Figure 3.…”
Section: Issues With the Back Stress Conceptmentioning
confidence: 99%
“…Several other authors reported the increase in strength by Hall-Petch strengthening in CNT/Al composites as well. [132,[147][148][149][150]…”
Section: Hall-petch Strengtheningmentioning
confidence: 99%
“…The heterogeneous structure is observed to produce an intrinsic synergetic strengthening, with its tensile strength much higher than that calculated by the rule of the mixture from separate layers, which is attributed to the macroscopic stress gradient and plastic incompatibility between layers [26,27]. For hierarchically structured metals with stable heterogeneous structures, their high ductility is attributed to extra strain hardening due to the presence of strain difference and the change of stress states, which generates GNDs and promotes the generation and interaction of dislocations [28]. As a result, the TiC p layer with a heterogeneous structure (PDZ and PRZ) provides extra strengthening effects.…”
Section: Discussionmentioning
confidence: 87%